2009
DOI: 10.1007/s12029-009-9090-y
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Obstruction and Pancreatitis Caused by Diffuse Nodular Hyperplasia of Brunner’s Gland

Abstract: Albeit its uncommon clinical presentation, it can become challenging in terms of diagnosis and management. A high index of suspicion is of paramount importance for establishing the correct diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Brunner's glands can be found throughout the duodenum; however, BGAs frequently occur more proximally and can be seen in association with acute/chronic duodenitis or erosive duodenitis [ 4 ]. BGH/BGAs are generally considered benign, and their malignant potential is unknown [ 6 ]. However, there are reports in the literature of occasional instances of malignancy developing in the background of BGH [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Brunner's glands can be found throughout the duodenum; however, BGAs frequently occur more proximally and can be seen in association with acute/chronic duodenitis or erosive duodenitis [ 4 ]. BGH/BGAs are generally considered benign, and their malignant potential is unknown [ 6 ]. However, there are reports in the literature of occasional instances of malignancy developing in the background of BGH [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 11% of BGH/BGA were found in asymptomatic patients [ 4 ]. Those that are symptomatic can present with occult or massive upper gastrointestinal bleeding or obstructive symptoms such as nausea, vomiting, abdominal pain, and early satiety [ 1 , 4 , 5 , 6 , 7 , 8 ]. Lesions in symptomatic patients also are typically larger in size [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations